Heart failure outcomes in Aboriginal and Torres Strait Islander peoples in the Hunter New England region of New South Wales. (1st July 2021) - McGee, Michael; Sugito, Stuart; Al-Omary, Mohammed S.; Hartnett, Darren; Senanayake, Tharindu; Hales, Kristy; Majeed, Tazeen; Ngo, Doan T.M.; Oakley, Patrick; Leitch, James W.; Sverdlov, Aaron L.; Boyle, Andrew J.
Abstract: Background Aboriginal and Torres Strait Islander suffer poor health outcomes, driven predominately by cardiovascular disease. Previous work has focused on remote communities although majority of Aboriginal and Torres Strait Islander patients live in urban New South Wales. We describe the heart failure characteristics and outcomes of the Aboriginal and Torres Strait Islander patients in Hunter New England Health, New South Wales, Australia. Methods A large retrospective, multi-centre cohort study from 2007 till 2016 in a geographically diverse Local Health District. The primary outcomes were all-cause mortality and all-cause readmission. The Aboriginal and Torres Strait Islander cohort was described by demographics, locality, and outcomes relative to the non-Indigenous patients from the same time period. Findings During the study period there were 20, 480 index admissions, of which 3.1% identified as Aboriginal and/or Torres Strait Islander. Aboriginal and Torres Strait Islander people admitted were younger by an average of 15 years (81 vs 66 years, p < 0.001), were more likely to live in a non-metropolitan locality (80 vs 61%, p < 0.001). Once adjustments were made for age, there was no significant difference in all-cause mortality. Indigenous status was a strong predictor of readmission on multivariate analysis, hazard ratio of 1.31 ( p < 0.001). Interpretation Aboriginal and Torres Strait Islander patients, compared to non-Indigenous patients, who are admitted with heart failure are younger, more commonly live in rural localities and suffer from a higher burden of comorbidities. Once adjustments are made for age and co-morbidities, indigenous status does not portend a worse outcome. Highlights: Aboriginal and Torres Strait Islander patients with HF are 15 years younger. Indigenous patients with HF suffer from more comorbidities and live rurally. Further work needs to be done to improve heart failure outcome disparity in Australia.